La Cofradía de los Negros de Huelva.: Bajo la advocación de Nuestra Señora del Rosario. - Calvo Lázaro, Rocío (Eikón / Imago, 2025)
This paper offers an insight into the history of the Brotherhood of the Blacks, which existed in Huelva from at least the 16th century until the first third of the 20th century, being the only ethnic brotherhood in the city. The research methodology involved analyzing existing publications, followed by investigating several archives in Huelva and Seville, focusing particularly on pastoral visits to the vicarage of Huelva, where the brotherhood was mentioned. This study examines the testaments, specifically analyzing the religious bequests, donations, alms, and burial practices of the testators to learn more about the brotherhood. Additionally, the study analyzes the brotherhood’s celebrations, heritage as well as its operation and organization. It is noteworthy that the Virgin of the Rosary was a highly venerated figure in Huelva, and her brotherhood was likely the oldest in the city.